EFFECTIVENESS OF MARKETING IN NICHE MARKETS: LIMITED RESOURCES AND A TARGETED AUDIENCE - Deberdiev Anvar Ravilevich , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This paper explores the effectiveness of marketing strategies in niche markets, where businesses operate with limited financial and human resources while targeting narrowly defined audiences. Through a qualitative multiple case study approach, the research identifies key success factors such as audience specificity, creative use of digital channels, and strategic adaptability. The findings highlight how resource constraints can drive innovation and customer loyalty when marketing efforts are focused, authentic, and value-driven.